One in two cancer patients is significantly distressed: Prevalence and indicators of distress. Issue 1 (16th June 2017) - Mehnert, A.; Hartung, T.J.; Friedrich, M.; Vehling, S.; Brähler, E.; Härter, M.; Keller, M.; Schulz, H.; Wegscheider, K.; Weis, J.; Koch, U.; Faller, H.
Abstract: Objective: Psychological distress is common in cancer patients, and awareness of its indicators is essential. We aimed to assess the prevalence of psychological distress and to identify problems indicative of high distress. Methods: We used the distress thermometer (DT) and its 34‐item problem list to measure psychological distress in 3724 cancer patients (mean age 58 years; 57% women) across major tumor entities, enrolled in an epidemiological multicenter study. To identify distress‐related problems, we conducted monothetic analyses. Results: We found high levels of psychological distress (DT ≥ 5) in 52% of patients. The most prevalent problems were fatigue (56%), sleep problems (51%), and problems getting around (47%). Sadness, fatigue, and sleep problems were most strongly associated with the presence of other problems. High distress was present in 81.4% of patients reporting all 3 of these problems (DT M  = 6.4). When analyzing only the subset of physical problems, fatigue, problems getting around, and indigestion showed the strongest association with the remaining problems and 76.3% of patients with all 3 problems were highly distressed (DT M  = 6.1). Conclusions: Our results show a high prevalence of psychological distress in cancer patients, as well as a set of problems that indicate the likely presence of other problems and high distress and can help clinicians identify distressed patients even if no routine distress screening is available.